Light-transmitting brick based on low-temperature light burning process and preparation method of light-transmitting brick

By processing the raw materials for translucent bricks using a low-temperature light-firing process, the problems of poor light transmittance and firing deformation have been solved, enabling the efficient production of ceramic bricks with high light transmittance and high strength.

CN120829295APending Publication Date: 2025-10-24GUANGDONG JIA MEI CERAMIC +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510967377.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-14
Publication Date
2025-10-24

AI Technical Summary

Technical Problem

Existing methods for preparing translucent ceramic tiles suffer from poor light transmittance and easy deformation during firing.

Method used

The process involves using a low-temperature light-burning method. This involves mixing mountain sand, high-whiteness water-milled tailings, lime particles, high-alumina clay, and barium carbonate, then adding water and ball milling to obtain a lean slurry. After spray granulation, the slurry is calcined at a low temperature and ground into a light-burned powder. This powder is then mixed with stone mud and ultra-white mud and ball-milled to form a body slurry. Finally, the slurry is granulated and pressed to obtain a translucent brick.

Benefits of technology

It improves light transmission, reduces deformation rate during high-temperature firing, increases the yield and strength of fired products, reduces firing costs, and enhances the color texture and pattern delicacy of the products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120829295A_ABST
    Figure CN120829295A_ABST
Patent Text Reader

Abstract

The invention provides a light-transmitting brick based on a low-temperature light burning process and a preparation method thereof, and the method comprises the following steps: according to a formula of a ceramic body, mixing Danshan sand, high-whiteness water mill tailings, lime particles, high alumina and barium carbonate, adding water, and carrying out ball milling to obtain barren slurry; carrying out spray granulation on the barren slurry to obtain barren powder, and calcining the barren powder in a preset low-temperature range to obtain a semi-finished product of a light calcined material; grinding the light calcined material semi-finished product to obtain light calcined material powder; mixing rubbed stone mud and ultra-white mud according to a formula of a ceramic green body, then performing slurrying to obtain slurry, mixing the light calcined material powder with the slurry, and then performing ball milling to obtain green body slurry; granulating the green body slurry to obtain green body powder, and treating the green body powder to obtain the light-transmitting brick. According to the invention, the light transmission performance, the firing yield and the product strength of the green body are improved, and the deformation rate during later high-temperature firing is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of ceramic production, in particular to a light-transmitting brick based on a low-temperature light-burning process and a preparation method thereof. BACKGROUND

[0002] As a wall decoration material of a building, ceramic tiles are widely used in indoor decoration and play a very important role in beautifying and decorating. With the improvement of people's living standards, the demand for the appearance of building decoration materials is also gradually increasing. Simply relying on the innovation of product patterns cannot meet the needs of consumers. In order to meet the needs of the market, it is necessary to improve the decoration effect of ceramic tiles, and one of the ways to improve the decoration effect of ceramic tiles is to have certain light-transmitting properties.

[0003] Due to reasons such as raw materials and processing technology, conventional ceramic tiles have many impurities, high porosity, large grain size and uneven distribution on the grain, impurities can absorb light, and impurities and small pores can scatter light. Larger grain size and uneven size distribution can also reduce the light-transmitting effect. Therefore, conventional ceramic tiles generally do not have light-transmitting properties and cannot meet people's pursuit of ceramic tiles in terms of transparency and visual change, such as light-transmitting background walls, light-transmitting staircases, and light-transmitting bars.

[0004] However, the existing light-transmitting ceramic tile preparation method generally has the problems of poor light-transmitting property and easy deformation during firing.

[0005] Therefore, the prior art has defects and needs to be improved and developed. SUMMARY

[0006] The technical problem to be solved by the present application is to provide a light-transmitting brick based on a low-temperature light-burning process and a preparation method thereof, aiming at solving the problems of poor light-transmitting property and easy deformation during firing of the existing light-transmitting ceramic tile preparation method.

[0007] The technical solution adopted by the present application to solve the technical problem is as follows:

[0008] The first aspect of the present application provides a light-transmitting brick preparation method based on a low-temperature light-burning process, wherein the method comprises:

[0009] According to the ceramic body formula, the Daxian sand, the high-white water mill tailings, the lime particles, the high-alumina soil and the barium carbonate are mixed and then ball milled with water to obtain a lean slurry;

[0010] The lean slurry is spray granulated to obtain a lean powder, and the lean powder is calcined at a predetermined low temperature range to obtain a light-burning material semi-finished product;

[0011] The light-burning material semi-finished product is ground to obtain a light-burning material powder;

[0012] The stone rubbing mud and the super white mud are mixed according to a ceramic body formula to obtain a slurry, and the light calcined material powder and the slurry are mixed and ball milled to obtain a body slurry;

[0013] The body slurry is granulated to obtain a body powder, and the body powder is treated to obtain a light-transmitting brick.

[0014] In an embodiment of the present application, the raw materials of the ceramic body formula include, by mass percentage:

[0015] Dashan sand 24-40%, high white water mill tailings 25-41%, lime particles 2-5%, high alumina soil 7-12%, barium carbonate 8-20%, stone rubbing mud 7-25%, and super white mud 5-10%.

[0016] In an embodiment of the present application, the chemical composition of the Dashan sand includes, by mass percentage:

[0017] SiO2: 45-55%, Al2O3: 20-30%, Fe2O3: 1-2%, CaO: 0-1%, MgO: 0-1%, K2O: 2-6%, Na2O: 0-1%, and loss on ignition 4-8%;

[0018] The chemical composition of the high white water mill tailings includes, by mass percentage:

[0019] SiO2: 50-60%, Al2O3: 15-25%, Fe2O3: 0-1%, CaO: 0-1%, MgO: 0-1%, K2O: 1-3%, Na2O: 2-5%, BaO: 7-15%, and loss on ignition 0-1%;

[0020] The chemical composition of the lime particles includes, by mass percentage:

[0021] SiO2: 1-5%, Al2O3: 0-2%, Fe2O3: 0-1%, CaO: 45-55%, MgO: 0-1%, K2O: 0-1%, Na2O: 0-1%, and loss on ignition 25-35%;

[0022] The chemical composition of the high alumina soil includes, by mass percentage:

[0023] SiO2: 40-50%, Al2O3: 40-50%, Fe2O3: 1-2%, CaO: 0-1%, MgO: 0-1%, K2O: 0-1%, Na2O: 0-1%, and loss on ignition 1-3%;

[0024] The chemical composition of the stone rubbing mud includes, by mass percentage:

[0025] SiO2: 60-70%, Al2O3: 1-5%, Fe2O3: 0-1%, CaO: 0-1%, MgO: 1-3%, K2O: 12-18%, Na2O: 1-2%, BaO: 1-4%, loss on ignition: 1-3%;

[0026] The chemical composition of the super-white clay includes, by mass percentage:

[0027] SiO2: 50-60%, Al2O3: 20-30%, Fe2O3: 0-1%, CaO: 0-1%, MgO: 0-1%, K2O: 2-5%, Na2O: 3-4%, loss on ignition: 2-6%.

[0028] In an embodiment of the present application, the chemical composition of the ceramic body formulation includes, by mass percentage:

[0029] SiO2: 55-68%, Al2O3: 14-18%, Fe2O3: 0-0.2%, CaO: 1-3%, MgO: 0-1%, K2O: 1-3%, Na2O: 1-3%, BaO: 7-15%, loss on ignition: 0.5-1.5%.

[0030] In an embodiment of the present application, the calcination of the dead-burned powder at a predetermined low temperature range obtains a semi-finished product of light-burned material, including:

[0031] The dead-burned powder is loaded into a saggar and fired at a temperature of 1000-1050°C to obtain a semi-finished product of light-burned material, wherein the end temperature of the quenching is 25-36°C and the cooling time is 10-15 min.

[0032] In an embodiment of the present application, the light-burned material powder and the slurry are mixed and ball-milled to obtain a body slurry, including:

[0033] The light-burned material powder and the slurry are mixed and ball-milled to obtain a body slurry, including:

[0034] In an embodiment of the present application, the opacifying agent includes any one or more of a colorant, zirconium silicate, and titanium dioxide;

[0035] The light-burned material powder and the slurry are mixed and ball-milled to obtain a body slurry, including:

[0036] When different types of opacifying agents are added, the light-burned material powder, the slurry, the water glass, the sodium silicate, and the different types of opacifying agents are mixed and ball-milled to obtain a body slurry with different colors and / or different light transmittances.

[0037] In an embodiment of the present application, the green body slurry is granulated to obtain a green body powder, and the green body powder is processed to obtain the light-transmitting brick.

[0038] The green body slurry with different colors and / or different light transmittances is granulated by using a centrifugal spray dryer to obtain green body powder with different colors and / or different light transmittances.

[0039] The green body powder with different colors and / or different light transmittances is mixed and distributed by a multi-tube roller distribution system, and is pressed and formed to obtain a ceramic green body, and the ceramic green body is processed to obtain the light-transmitting brick.

[0040] In an embodiment of the present application, the light-transmitting brick has a sintering temperature of 1150-1220℃ and a sintering cycle of 50-90min; the light-transmitting brick has a Vickers hardness of 700-800HV, a light transmittance of 8-10%, a whiteness of 75°-85°, and a fracture modulus of 50-60MPa.

[0041] The second aspect of the present application provides a light-transmitting brick, wherein the light-transmitting brick is prepared by the light-transmitting brick preparation method based on the low-temperature light-burning process.

[0042] The present application discloses a light-transmitting brick and a preparation method based on a low-temperature light-burning process. The method comprises the following steps: according to a ceramic green body formula, mixing Daxian sand, high-white water mill tailings, lime particles, high-alumina soil and barium carbonate, and then ball-milling after adding water to obtain a barren slurry; after spray granulation of the barren slurry, a barren powder is obtained, and the barren powder is calcined at a predetermined low temperature range to obtain a light-burning material semi-finished product; the light-burning material semi-finished product is ground to obtain a light-burning material powder; according to the ceramic green body formula, stone rubbing mud and super-white mud are mixed and slurried to obtain a mud slurry, and the light-burning material powder and the mud slurry are mixed and ball-milled to obtain a green body slurry; the green body slurry is granulated to obtain a green body powder, and the green body powder is processed to obtain the light-transmitting brick. In the present application, the barren raw material is light-burned at a low temperature, so that the raw material is close to a sintering critical point un-ceramization state. In this state, the raw material will not be completely sintered and ceramized due to high temperature, thereby causing the problem that the raw material is not easy to break and shape. The light-burning can promote the partial crystal type conversion of the barren raw material, so that more crystal types are converted into glass phase or crystal with a refractive index close to glass phase in the subsequent sintering process, thereby improving the light-transmitting performance of the green body, reducing the deformation rate in the later high-temperature sintering, and improving the sintering yield and product strength. Moreover, the light-burning material powder is mixed and ball-milled with the mud slurry for the second time, the crystal produced by the ball-milling is further broken into smaller and more uniform crystals, and the iron substance is further precipitated, which can further promote the generation of glass phase in the sintering of the light-transmitting brick, thereby improving the light-transmitting performance of the green body. BRIEF DESCRIPTION OF DRAWINGS

[0043] Figure 1 is a flow chart of a preferred embodiment of a light-transmitting brick preparation method based on a low-temperature light-burning process in the present application. DETAILED DESCRIPTION

[0044] To make the objectives, technical solutions, and advantages of the present application clearer and more explicit, the present application is further described in detail below with reference to the drawings and examples. It should be understood that the specific examples described herein are only used to explain the present application and do not limit the present application.

[0045] Although light-transmitting bricks have outstanding features, under the condition of good light-transmitting performance, there are often problems such as that green bricks are prone to deformation, the yield of fired products is low, the strength of products is low, the surface pattern of products can only float on the surface under the action of light, the stereoscopic effect of the pattern is not strong enough, and it is difficult to achieve the color quality and the delicacy of the pattern of natural stone under the light.

[0046] Currently, some light-transmitting brick preparation methods include: "step A, 200℃-400℃ firing after mixing of light-transmitting materials → step B, ball milling and spray granulation of pre-prepared materials → step C, compression molding → step D, grinding of green bricks → step E, inkjet → step F, glazing → step G, three times of firing → step H, polishing", the technical solution of which is to reduce organic impurities in light-transmitting raw materials and improve the plasticity of the raw materials by calcination at 200℃-400℃, and to improve the deformation of the ceramic tile and the strength of the ceramic tile by three times of slow firing, but there are still some deficiencies, specifically including:

[0047] 1. Large volume shrinkage and low density during the firing process of the ceramic tile. The pre-calcination of the raw materials cannot effectively reduce the volume shrinkage, and the calcination at 200℃-400℃ can only reduce the organic impurities in the raw materials, and cannot effectively decompose the inorganic carbonates, with a high loss on ignition of 3-6%.

[0048] 2. Slow firing cycle and high firing cost. Although the three times of slow firing effectively solves the problems of easy deformation of green bricks and low yield of fired products, the firing cycle needs 3-8 hours, and the production cost is also increased.

[0049] 3. The texture light and dark levels are not distinct enough. The light-transmitting materials used are single, and the surface pattern of the products can only float on the surface under the light, and the stereoscopic effect of the pattern is not strong enough.

[0050] 4. The light-transmitting property is slightly poor. The volume shrinkage is large, the porosity is still large, and the grain size is large, resulting in weak light-transmitting property.

[0051] Some light-transmitting brick preparation methods include: "step A, light-transmitting material is mixed and fired at 1300-1400 DEG C -> step B, precast material is crushed into particles -> step C, compression molding -> step D, grinding -> step E, inkjet -> step F, glazing -> step G, secondary firing -> step H, polishing", the process only solves the problems of large volume shrinkage and low density during the firing of the ceramic tile, and the precast material after firing at 1300-1400 DEG C has been completely vitrified, the plasticity of the prepared powder is poor, the firing period is shortened, but also needs 3-5 hours, and the texture bright and dark levels are not clear enough, and the particle size of the prepared powder is large (100-150 mesh, i.e. 109-150 microns). Because the powder has been vitrified, the voids of the ceramic tile after compression are basically unchanged, and the grain size is large, resulting in poor light-transmitting performance. Therefore, the existing technology has the problems of poor light-transmitting performance, long firing period, poor plasticity of the body material, and large shrinkage of the body.

[0052] The technical problem to be solved by the present application is to provide a light-transmitting brick preparation method based on a low-temperature light firing process to solve the problems of poor plasticity of the body material, large shrinkage of the body, slow firing period, and poor light-transmitting performance.

[0053] Please refer to Figure 1 , Figure 1 is the flowchart of the light-transmitting brick preparation method in the present application. As Figure 1 shown, it includes the following steps:

[0054] Step S100, according to the ceramic body formula, the Dasyan sand, the high white water tailings, the lime particles, the high alumina soil, and the barium carbonate are mixed and then ball milled with water to obtain a lean slurry;

[0055] Step S200, the lean slurry is spray granulated to obtain a lean powder, and the lean powder is calcined at a predetermined low temperature range to obtain a light calcined semi-finished product;

[0056] Step S300, the light calcined semi-finished product is ground to obtain a light calcined powder;

[0057] Step S400, the stone mud and the super white mud are mixed according to the ceramic body formula to obtain a slurry, and the light calcined powder and the slurry are mixed and then ball milled to obtain a body slurry;

[0058] Step S500, the body slurry is granulated to obtain a body powder, and the body powder is treated to obtain a light-transmitting brick.

[0059] Specifically, in step S100, the barren raw materials Dasyan sand, high white water mill tailings, lime particles, high alumina soil, and barium carbonate are mixed uniformly by adding water in a ball mill at a preset mass percentage, and iron is removed through a 150-mesh screen.

[0060] In step S200, the barren powder is calcined at a predetermined low temperature range to make the raw material approach a sintering critical point un-ceramization state, which does not cause the raw material to sinter completely ceramized due to excessively high temperature, thereby causing the problem that the raw material is not easy to break and shape. Since the calcination can promote the partial crystal transformation of the barren raw material, more crystal forms are transformed into glass phase or crystal with a refractive index close to that of glass phase in the subsequent firing process, thereby improving the light transmission performance of the body, reducing the deformation rate during high-temperature firing in the later stage, and improving the firing yield and product strength.

[0061] In step S300, the calcined semi-finished light calcined material is sent to a Raymond mill for grinding to obtain light calcined material powder, and is stored for use after screening.

[0062] In step S400, the stone rubbing mud and ultra-white mud are subjected to slurry treatment to remove iron and impurities through a 150-mesh screen to obtain more pure mud slurry and store it for use.

[0063] The Dasyan sand, high white water mill tailings, lime particles, high alumina soil, and barium carbonate in the ceramic body formula of the present application all belong to barren raw materials, and the stone rubbing mud and ultra-white mud belong to adhesive raw materials. The barren and adhesive raw materials in the body formula are processed separately, the barren raw materials are calcined first, and the adhesive raw materials are subjected to slurry treatment, then the two are mixed and ball milled to prepare the pre-processing process of the powder, which can ensure the forming performance of the body. That is, the order of the steps of preparing the light calcined material powder and preparing the mud slurry can be exchanged, the light calcined material powder can be prepared first, and then the mud slurry mixed with the stone rubbing mud and ultra-white mud can be prepared; or the mud slurry mixed with the stone rubbing mud and ultra-white mud can be prepared first, and then the light calcined material powder can be prepared; or the two steps can be performed simultaneously.

[0064] The embodiment of the present application calcines the barren raw material at a low temperature to make the raw material approach a sintering critical point un-ceramization state, which does not cause the raw material to sinter completely ceramized due to excessively high temperature, thereby causing the problem that the raw material is not easy to break and shape. The calcination can promote the partial crystal transformation of the barren raw material, more crystal forms are transformed into glass phase or crystal with a refractive index close to that of glass phase in the subsequent firing process, thereby improving the light transmission performance of the body, reducing the deformation rate during high-temperature firing in the later stage, and improving the firing yield and product strength. Moreover, the light calcined material powder is subjected to secondary mixing and ball milling with the mud slurry, the crystals generated by the ball milling are further broken into smaller and more uniform crystals, the iron substances are further precipitated, which is more conducive to the generation of glass phase in the firing of the light transmission brick, thereby improving the light transmission performance of the body.

[0065] In the embodiment of the present application, the raw materials of the ceramic body formula include, in percentage by mass:

[0066] Dasye sand 24-40%, high white water mill tailings 25-41%, lime particles 2-5%, high bauxite 7-12%, barium carbonate 8-20%, stone rubbing mud 7-25%, and super white mud 5-10%.

[0067] In one specific embodiment, the raw materials of the ceramic body formula include, in percentage by mass: Dasye sand 32%, high white water mill tailings 33%, lime particles 4%, high bauxite 9%, barium carbonate 7%, stone rubbing mud 9%, and super white mud 6%.

[0068] The ceramic body formula of the embodiment of the present application includes a refractory raw material and a viscous raw material, and the refractory raw material and the viscous raw material are treated respectively, so as to improve the light transmission performance of the body and reduce the deformation rate during high-temperature firing later.

[0069] In one embodiment of the present application, the chemical composition of the Dasye sand includes, in percentage by mass:

[0070] SiO2: 45-55%, Al2O3: 20-30%, Fe2O3: 1-2%, CaO: 0-1%, MgO: 0-1%, K2O: 2-6%, Na2O: 0-1%, and loss on ignition 4-8%;

[0071] The chemical composition of the high white water mill tailings includes, in percentage by mass:

[0072] SiO2: 50-60%, Al2O3: 15-25%, Fe2O3: 0-1%, CaO: 0-1%, MgO: 0-1%, K2O: 1-3%, Na2O: 2-5%, BaO: 7-15%, and loss on ignition 0-1%;

[0073] The chemical composition of the lime particles includes, in percentage by mass:

[0074] SiO2: 1-5%, Al2O3: 0-2%, Fe2O3: 0-1%, CaO: 45-55%, MgO: 0-1%, K2O: 0-1%, Na2O: 0-1%, and loss on ignition 25-35%;

[0075] The chemical composition of the high bauxite includes, in percentage by mass:

[0076] SiO2: 40-50%, Al2O3: 40-50%, Fe2O3: 1-2%, CaO: 0-1%, MgO: 0-1%, K2O: 0-1%, Na2O: 0-1%, and loss on ignition 1-3%;

[0077] The chemical composition of the stone rubbing mud includes, in percentage by mass:

[0078] SiO2: 60-70%, Al2O3: 1-5%, Fe2O3: 0-1%, CaO: 0-1%, MgO: 1-3%, K2O: 12-18%, Na2O: 1-2%, BaO: 1-4%, loss on ignition: 1-3%;

[0079] The chemical composition of the super white mud includes, in percentage by mass:

[0080] SiO2: 50-60%, Al2O3: 20-30%, Fe2O3: 0-1%, CaO: 0-1%, MgO: 0-1%, K2O: 2-5%, Na2O: 3-4%, loss on ignition: 2-6%.

[0081] The chemical composition of the barium carbonate includes, in percentage by mass: BaO: 80-90%, loss on ignition: 10-20%.

[0082] The Dashan sand in the embodiments of the present application helps to adjust the plasticity of the body and provide certain skeleton support in the firing process, reducing the shrinkage and deformation of the body. The high white water mill tailings contain high SiO2 and Al2O3, which helps to improve the whiteness and mechanical strength of the body. At the same time, the recycling of the tailings also helps to reduce the production cost and realize the recycling of resources. The lime particles mainly play the role of flux in the ceramic body, which can reduce the firing temperature, shorten the firing time, and improve the thermal expansion coefficient of the body, which is beneficial to the body-glaze combination. The high alumina contains high Al2O3 component, which helps to improve the chemical stability and thermal stability of the body. At high temperature, the high alumina can form stable mineral phases such as mullite, which enhances the mechanical strength and thermal shock resistance of the body. Barium carbonate in the ceramic body can improve the whiteness and gloss of the ceramic. The SiO2 content in the stone rubbing mud is very high, which helps to improve the strength and hardness of the body and ensure the structural stability of the body during forming and firing. The super white mud can improve the whiteness and texture of the product.

[0083] In the embodiments of the present application, the chemical composition of the ceramic body formula includes, in percentage by mass:

[0084] SiO2: 55-68%, Al2O3: 14-18%, Fe2O3: 0-0.2%, CaO: 1-3%, MgO: 0-1%, K2O: 1-3%, Na2O: 1-3%, BaO: 7-15%, loss on ignition: 0.5-1.5%.

[0085] In one specific embodiment, the chemical composition of the ceramic body formula includes, in percentage by mass: SiO2: 67.28%, Al2O3: 16.64%, Fe2O3: 0.15%, CaO: 1.84%, MgO: 0.28%, K2O: 2.66%, Na2O: 1.98%, BaO: 8.23%, loss on ignition: 0.94%.

[0086] In the embodiments of the present application, SiO2provides the basic framework of the body, which helps to improve the strength and hardness of the body, and its content is between 55-68%, which can ensure that the body has sufficient mechanical strength to withstand various stresses in the subsequent processing and firing process. Al2O3can significantly improve the chemical stability and thermal stability of the body, and its content is between 14-18%, which helps the body to maintain structural stability at high temperature and reduces the risk of deformation and cracking. CaO, MgO, K2O, Na2O play a fluxing role in the firing process, which can reduce the sintering temperature of the body and promote the densification of the body. BaO can adjust the sintering performance and physical properties of the body, and its content is between 7-15%, which helps the body to form a uniform microstructure during firing and improves the density and mechanical strength of the body. Fe2O3is a coloring oxide in ceramic body, and low content of Fe2O3helps to produce ceramic products with pure color and high whiteness.

[0087] In the embodiments of the present application, the calcination of the refractory powder at a predetermined low temperature range obtains a lightly calcined semi-finished product, which includes:

[0088] The refractory powder is loaded into the saggar, and the lightly calcined semi-finished product is obtained by firing at a temperature of 1000-1050℃, wherein the end point temperature of the quenching is 25-36℃, and the cooling time is 10-15min.

[0089] In the embodiments of the present application, the refractory raw material in the light-transmitting brick body is lightly calcined at a low temperature of 1000-1050℃, which makes the raw material close to the sintering critical point without vitrification. This state does not cause the raw material to sinter completely and vitrify due to high temperature (1200-1400℃), which in turn causes the raw material to be difficult to break and shape. Since light calcination can promote partial crystal transformation of the refractory raw material, more crystal forms are transformed into glass phase or crystal with refractive index close to glass phase in the subsequent firing process, thereby improving the light transmission performance of the body and reducing the deformation rate during high temperature firing, improving the firing yield and product strength.

[0090] In the embodiments of the present application, the lightly calcined material powder and the mud are mixed and ball milled to obtain a body slurry, which includes:

[0091] The light calcined material powder and the slurry are mixed, and water glass, sodium silicate and a creaming agent are added, and the ball milling is performed to a fineness of 325 mesh residue less than or equal to 0.3-1% to obtain the green body slurry.

[0092] Specifically, the light calcined material powder and the slurry are mixed according to the preset weight ratio, and 1-2% of water glass, 3-5% of sodium silicate and a creaming agent (colorant, zirconium silicate, titanium dioxide, etc.) are added, and the ball milling is performed to a fineness of 325 mesh residue less than or equal to 0.3-1% to obtain the green body slurry, and the green body slurry is further sieved to remove iron.

[0093] In the embodiment of the present application, the creaming agent includes any one or more of a colorant, zirconium silicate and titanium dioxide.

[0094] In the embodiment of the present application, the creaming agent includes any one or more of a colorant, zirconium silicate and titanium dioxide.

[0095] The light calcined material powder and the slurry are mixed, and water glass, sodium silicate and a creaming agent are added, and the ball milling is performed to a fineness of 325 mesh residue less than or equal to 0.3-1% to obtain the green body slurry.

[0096] When different types of creaming agents are added, the light calcined material powder, the slurry, the water glass, the sodium silicate and the different types of creaming agents are mixed and ball milled to obtain the green body slurry with different colors and / or different transmittances.

[0097] In the embodiment of the present application, different types of creaming agents are added to obtain the green body slurry with different colors and / or different transmittances, so that a plurality of green body powders with different transmittances and different colors are obtained based on the green body slurry with different colors and / or different transmittances, and then the textured and bright-dark level clear and pattern effect rich polished wear-resistant and transmittance products are obtained.

[0098] In the embodiment of the present application, the green body slurry is granulated to obtain the green body powder, and the green body powder is processed to obtain the transmittance brick, including:

[0099] The centrifugal spray dryer is used to granulate the green body slurry with different colors and / or different transmittances to obtain the green body powder with different colors and / or different transmittances.

[0100] The green body powders with different colors and / or different transmittances are mixed and distributed by the multi-tube roller distribution system, and are pressed and formed to obtain the ceramic green body, and the ceramic green body is processed to obtain the transmittance brick.

[0101] Specifically, the centrifugal spray dryer is used for granulation, the liquid is dispersed into tiny mist droplets by the centrifugal force of high-speed rotation, and then the mist droplets are rapidly dried by hot air to form solid particles, and the fineness can reach 10-150 microns.

[0102] The prepared body powder includes: a base light-transmitting material, different light-transmitting rate body materials, and different color category body materials, which are respectively stored in standby bins. The different light-transmitting rate and different color category body materials are transported to the distributor according to production conditions and process requirements, and are distributed and pressed by using the multi-tube roller distribution system. The distribution and application mode can be determined according to production conditions and process requirements, and multiple different light-transmitting rate and different color category body materials are simultaneously applied to the light-transmitting brick product. The pressure of the pressed forming is 120-160 MPa.

[0103] In the embodiment of the application, multiple different light-transmitting rate and different color category body materials are simultaneously applied to the product by using the multi-tube roller distribution system, so that a textured light-and-dark level clear and pattern effect rich polished wear-resistant light-transmitting product is obtained.

[0104] In the embodiment of the application, the sintering temperature of the light-transmitting brick is 1150-1220 ℃, and the sintering period is 50-90 min.

[0105] The light-transmitting brick provided in the embodiment of the application has low sintering temperature, short sintering period, improved production efficiency, and reduced production cost.

[0106] The application further provides a light-transmitting brick, which is prepared by the light-transmitting brick preparation method based on the low-temperature light-burning process.

[0107] The following specific embodiments are listed for illustration.

[0108] Embodiment one:

[0109] The raw materials of the ceramic body formula in the embodiment include, by mass percentage:

[0110] Dasyan sand 32%; high white water mill tailings 32%; lime particles 4%; high alumina soil 9%; barium carbonate 7%; stone rubbing mud 10%; super white mud 6%.

[0111] The light-transmitting brick preparation steps in the embodiment include:

[0112] Step A1, the materials except the stone rubbing mud and the super white mud are mixed uniformly by adding water and ball milling, and then iron is removed by passing through a 150-mesh sieve. The obtained slurry is loaded into a kiln made of refractory material, heated to 1050 ℃, and quenched to 36 ℃ within 15 min to obtain a light-burning material semi-finished product;

[0113] Step A2, the calcined light-burning material semi-finished product is sent to a Raymond mill for grinding and crushing to obtain a light-burning material powder with a particle size of 150-250 mesh, and iron is removed by sieving and stored for standby use; at the same time, the stone rubbing mud and the super white mud are subjected to a slurry processing process, iron is removed by passing through a 150-mesh sieve, and a mud slurry is obtained and stored for standby use;

[0114] Step A3, the standby light calcined material powder and mud are added into the auxiliary agent for ball milling according to the preset weight ratio, and a slurry with a fineness residue of less than or equal to 0.3-1% is obtained by passing through a 325 mesh screen, and then the slurry is aged and granulated by a centrifugal spray dryer to obtain a powder with a fineness of 10-150 microns;

[0115] Step A4, the powder is distributed through a multi-tube roller distribution system, and is pressed into a green brick under the condition of 130 MPa;

[0116] Step A5, the green brick is sent into a kiln for firing, the firing temperature is 1175℃, the firing period is 90 min, and then the product is polished.

[0117] The chemical composition of the light-transmitting brick measured in this embodiment includes, in terms of mass percentage: SiO2: 67.28%, Al2O3: 16.64%, Fe2O3: 0.15%, CaO: 1.84%, MgO: 0.28%, K2O: 2.66%, Na2O: 1.98%, BaO: 8.23%, and loss on ignition: 0.94%.

[0118] Example Two:

[0119] The raw materials of the ceramic body formula of this embodiment include, in terms of mass percentage:

[0120] Dashan sand 25%; high white water mill tailings 35%; lime particles 3%; high alumina soil 8%; barium carbonate 12%; stone rubbing mud 7%; super white mud 10%.

[0121] The preparation steps of the light-transmitting brick of this embodiment include:

[0122] Step B1, the materials except the stone rubbing mud and the super white mud are ball-mixed with water, and then iron is removed by passing through a 150 mesh screen, and the obtained slurry is loaded into a refractory-made crucible, heated to 1050℃, and quenched to 30℃ within 15 min to obtain a light calcined material semi-product;

[0123] Step B2, the calcined light calcined material semi-product is sent into a Raymond mill for grinding and crushing to obtain a light calcined material powder with a particle size of 150-250 mesh, and iron is removed by passing through a screen and stored for standby use; at the same time, the stone rubbing mud and the super white mud are subjected to a slurry-making process, iron is removed by passing through a 150 mesh screen, and a mud slurry is obtained and stored for standby use;

[0124] Step B3, the standby light calcined material powder and mud are added into the auxiliary agent for ball milling according to the preset weight ratio, and a slurry with a fineness residue of less than or equal to 0.3-1% is obtained by passing through a 325 mesh screen, and then the slurry is aged and granulated by a centrifugal spray dryer to obtain a powder with a fineness of 10-150 microns;

[0125] Step B4, the powder is distributed by a multi-tube roller distribution system, and is pressed into a green brick under the condition of 140 MPa;

[0126] Step B5, the green brick is sent into a kiln for firing, a firing temperature is 1218℃, a firing period is 50 min, and then the product is polished.

[0127] The chemical composition of the light-transmitting brick measured in the embodiment includes, in percentage by mass: SiO2: 62.52%, Al2O3: 15.43%, Fe2O3: 0.18%, CaO: 1.38%, MgO: 0.2%, K2O: 3.00%, Na2O: 2.20%, BaO: 14.11%, and a loss on ignition of 0.98%.

[0128] Example Three

[0129] The raw materials of the ceramic body formula of the embodiment include, in percentage by mass:

[0130] Dasyan sand 35%; high white water mill tailings 26%; lime particles 3%; high alumina soil 7%; barium carbonate 9%; stone rubbing mud 12%; and super white mud 8%.

[0131] The preparation steps of the light-transmitting brick of the embodiment include:

[0132] Step C1, the materials except the stone rubbing mud and the super white mud are ball-mixed with water, uniformly mixed, and then iron is removed through a 150-mesh sieve, the obtained slurry is loaded into a refractory-made sagger, heated to 1050℃, and then quenched to 30℃ within 15 min to obtain a calcined semi-finished product;

[0133] Step C2, the calcined semi-finished product is sent into a Raymond mill for grinding and crushing to obtain a calcined powder with a particle size of 150-250 mesh, and iron is removed through a sieve for storage; at the same time, the stone rubbing mud and the super white mud are removed through a 150-mesh sieve for iron removal through a slurry process to obtain a mud slurry for storage;

[0134] Step C3, the prepared calcined powder and the mud slurry are ball-mixed with auxiliary agents according to a preset weight ratio, and then a slurry with a fineness residue of less than or equal to 0.3-1% is obtained through a 325-mesh sieve, and then the slurry is aged and used to obtain a powder with a fineness of 10-150 microns through a centrifugal spray dryer;

[0135] Step C4, the powder is distributed by a multi-tube roller distribution system, and is pressed into a green brick under the condition of 120 MPa;

[0136] Step C5, the green brick is sent into a kiln for firing, a firing temperature is 1195℃, a firing period is 75 min, and then the product is polished.

[0137] The chemical composition of the light-transmitting brick measured in the embodiment includes, in percentage by mass: SiO2: 65.78%, Al2O3: 16.44%, Fe2O3: 0.1%, CaO: 1.64%, MgO: 0.32%, K2O: 2.25%, Na2O: 1.66%, BaO: 10.58%, loss on ignition: 1.23%.

[0138] The test results of the polished light-transmitting bricks obtained in Examples 1, 2 and 3 are shown in Table 1.

[0139] Table 1

[0140]

[0141] The Vickers hardness HV0.5 of the light-transmitting brick of the application is 700-800HV, the light transmittance is 8-10%, the whiteness is 75-85°, and the modulus of rupture is 50-60MPa.

[0142] Therefore, the application improves the firing yield, product strength, whiteness, light-transmitting performance, improves the deformation of the brick body, reduces the firing cost, and significantly improves the color quality and the fineness of the pattern of the product, and solves the problems of poor plasticity of the green body, large shrinkage of the green body, long firing period and poor light-transmitting performance.

[0143] The application provides a light-transmitting brick based on a low-temperature light-burning process and a preparation method, the method comprising: mixing Daxian sand, high-white water-milling tailings, lime particles, high-alumina soil and barium carbonate, ball-milling after adding water, to obtain a lean slurry; spray granulating the lean slurry to obtain a lean powder, calcining the lean powder in a predetermined low-temperature range to obtain a light-burned semi-finished product; grinding the light-burned semi-finished product to obtain a light-burned powder; mixing stone-mixed mud and super-white mud according to a ceramic green body formula to obtain a slurry, and ball-milling the light-burned powder and the slurry to obtain a green body slurry; granulating the green body slurry to obtain a green body powder, and processing the green body powder to obtain a light-transmitting brick. The application burns lean raw materials at a low temperature, so that the raw materials are close to the sintering critical point and are not vitrified, which does not cause the raw materials to be completely sintered and vitrified due to excessively high temperature, and thus the raw materials are not easy to break and shape. The light burning promotes the partial crystal transformation of the lean raw materials, so that more crystal forms are transformed into glass phase or crystal with a refractive index close to that of glass phase in the subsequent firing process, thereby improving the light-transmitting performance of the green body, reducing the deformation rate during high-temperature firing, and improving the firing yield and product strength. Moreover, the light-burned powder is ball-milled with the slurry for the second time, the crystal generated by the ball-milling is further broken into smaller and more uniform crystals, iron substances are further precipitated, the generation of glass phase in the firing of the light-transmitting brick is further promoted, and thus the light-transmitting performance of the green body is improved.

[0144] It is to be understood that the application is not limited to the examples described above, which can be modified or adapted in several ways by those skilled in the art without departing from the scope of the present application, as defined by the appended claims.

Claims

1. A method for preparing a light-transmitting brick based on a low-temperature light-burning process, characterized in that, The method comprises: According to the ceramic body formula, the Dashan sand, the high white water mill tailings, the lime particles, the high alumina soil and the barium carbonate are mixed, then water is added for ball milling to obtain a lean slurry; After the lean slurry is spray granulated, a lean powder is obtained, and the lean powder is calcined at a predetermined low temperature range to obtain a lightly calcined material semi-product; The lightly calcined material semi-product is ground to obtain a lightly calcined material powder; According to the ceramic body formula, the stone rubbing mud and the super white mud are mixed to obtain a mud slurry, and the lightly calcined material powder and the mud slurry are mixed and ball milled to obtain a body slurry; The body slurry is granulated to obtain a body powder, and the body powder is treated to obtain a light-transmitting brick.

2. The method for preparing light-transmitting brick based on low-temperature lightly fired process according to claim 1, characterized in that, The raw materials of the ceramic body formula include, by mass percentage: 24-40% of the Dashan sand, 25-41% of the high white water mill tailings, 2-5% of the lime particles, 7-12% of the high alumina soil, 8-20% of the barium carbonate, 7-25% of the stone rubbing mud and 5-10% of the super white mud.

3. The method for preparing light-transmitting brick based on low-temperature light-burning process according to claim 2, characterized in that, The chemical composition of the Dashan sand includes, by mass percentage: 45-55% of SiO2, 20-30% of Al2O3, 1-2% of Fe2O3, 0-1% of CaO, 0-1% of MgO, 2-6% of K2O, 0-1% of Na2O and 4-8% of loss on ignition; The chemical composition of the high white water mill tailings includes, by mass percentage: 50-60% of SiO2, 15-25% of Al2O3, 0-1% of Fe2O3, 0-1% of CaO, 0-1% of MgO, 1-3% of K2O, 2-5% of Na2O, 7-15% of BaO and 0-1% of loss on ignition; The chemical composition of the lime particles includes, by mass percentage: 1-5% of SiO2, 0-2% of Al2O3, 0-1% of Fe2O3, 45-55% of CaO, 0-1% of MgO, 0-1% of K2O, 0-1% of Na2O and 25-35% of loss on ignition; The chemical composition of the high alumina soil includes, by mass percentage: 40-50% of SiO2, 40-50% of Al2O3, 1-2% of Fe2O3, 0-1% of CaO, 0-1% of MgO, 0-1% of K2O, 0-1% of Na2O and 1-3% of loss on ignition; The chemical composition of the stone rubbing mud includes, by mass percentage: 60-70% of SiO2, 1-5% of Al2O3, 0-1% of Fe2O3, 0-1% of CaO, 1-3% of MgO, 12-18% of K2O, 1-2% of Na2O, 1-4% of BaO and 1-3% of loss on ignition; The chemical composition of the super white mud includes, by mass percentage: 50-60% of SiO2, 20-30% of Al2O3, 0-1% of Fe2O3, 0-1% of CaO, 0-1% of MgO, 2-5% of K2O, 3-4% of Na2O and 2-6% of loss on ignition.

4. The method for preparing light-transmitting brick based on low-temperature lightly fired process according to claim 1, characterized in that, The chemical composition of the ceramic body formula includes, by mass percentage: SiO2: 55-68%, Al2O3: 14-18%, Fe2O3: 0-0.2%, CaO: 1-3%, MgO: 0-1%, K2O: 1-3%, Na2O: 1-3%, BaO: 7-15%, loss on ignition: 0.5-1.5%.

5. The method for preparing light-transmitting brick based on low-temperature lightly fired process according to claim 1, characterized in that, calcining the said lean powder at a predetermined low temperature range to obtain a semi-finished product of lean-burned material, including: loading the said lean powder into a sagger and firing at a temperature of 1000-1050℃ to obtain a semi-finished product of lean-burned material, wherein the end temperature of the quenching is 25-36℃ and the cooling time is 10-15min.

6. The method for preparing light-transmitting brick based on low-temperature lightly fired process according to claim 1, characterized in that, mixing the said lean-burned material powder and the slurry and ball-milling to obtain a body slurry, including: mixing the said lean-burned material powder and the slurry and adding sodium silicate, sodium silicate and a creaming agent, and ball-milling to a fineness of 325 mesh residue less than or equal to 0.3-1% to obtain a body slurry.

7. The method for producing light transmitting bricks based on low-temperature light-burning process according to claim 6, characterized in that, the creaming agent includes any one or more of a colorant, zirconium silicate and titanium dioxide; mixing the said lean-burned material powder and the slurry and ball-milling to obtain a body slurry, further including: when different types of creaming agents are added, the said lean-burned material powder, the slurry, the sodium silicate and the different types of creaming agents are mixed and ball-milled to obtain body slurries with different colors and / or different light transmittances.

8. The method for preparing light-transmitting brick based on low-temperature light-burning process according to claim 7, characterized in that, granulating the said body slurry to obtain a body powder, and processing the said body powder to obtain a light-transmitting brick, including: granulating the body slurries with different colors and / or different light transmittances using a centrifugal spray dryer to obtain body powders with different colors and / or different light transmittances; mixing and distributing the body powders with different colors and / or different light transmittances through a multi-tube roller distribution system and pressing to form a ceramic body, and processing the said ceramic body into a light-transmitting brick.

9. The method for preparing light-transmitting brick based on low-temperature lightly fired process according to claim 1, characterized in that, The light-transmitting brick has a firing temperature of 1150-1220℃ and a firing period of 50-90min, a Vickers hardness of 700-800HV, a light transmittance of 8-10%, a whiteness of 75°-85° and a modulus of rupture of 50-60MPa.

10. A light-transmitting brick, characterized in that The light-transmitting brick is prepared by the method for preparing a light-transmitting brick based on a low-temperature lean-burning process according to any one of claims 1-9.